Estimation, zoning and sensitive analyses of forest productivity of Eucalyptus in northeast Saõ Paulo using the 3-PG model - Zani Lemos, Cristiane Camargo; Hakamada, Rodrigo Eiji; Carrero, Omar; Alvares, Clayton Alcarde; Stape, José Luiz [UNESP] (My University, 2018)
The productivity zoning at the landscape level can help forest managers on land use decision making, based on correct area selection for the crop. The goal of this research was to estimate and generate a Eucalyptus productivity zoning of Sao Paulo state northeast and to determine the main limiting factors to growth based on model (temperature, frost, vapor deficit pressure, available soil water, and soil fertility). Productivity estimation was done using the model 3-PG, using as inputs estimated rainfall, maximum a minimum temperatures and soil maps. To validate the model, were compared the mean annual increment at 7 years (MAI 7) estimated by 3-PG with the inventory projection (forest with 5 to 8 years), corresponding around 58,000 ha. The average of all validated area was similar between the 3-PG estimation (41.9 m3 ha-1ano-1) and inventory projection, (44.1 m3 ha-1ano-1). However, when the comparison of the IMA7 between measured and predicted, stratified by soil type and farm was done, we found high data dispersion, probably because of the average climatic data used as model input, soil type detailing reflecting the soil water content, genetic material adaptation and silviculture management, or interaction of those factors. The results suggested that increase the analytical scale reduce the precision of the estimates. It was possible to make the zoning of the real productivity of Eucalyptus in the northeastern state of Saõ Paulo. The most productivity areas were located at south. The main growth constraints were vapor pressure deficit and soil water content.
Estimacaõ, zoneamento e análise de sensibilidade da produtividade florestal de Eucalyptus no Nordeste do Estado de Saõ Paulo através do modelo 3-PG
Keywords: 3-PG model; Geographic Information System; Limiting growth factors; Mean annual increment